About the Feuilleton Strategy of "Wycinanki" (Cutouts). In Reply to Prof. Henryk Mamzer - Wrzosek, Wojciech (Sensus Historiae, 2023)
The author responds to Prof. Henryk Mamzer’s ample review of his collection of sketches, entitled Wycinanki. He refers to three topics raised by the critic: the author’s alleged panhistoricism, the discussion of the thesis that everything is historical and even nothing is historical and, extensively, to Fernand Braudel’s concept of material culture.